The artistry of anger : black and white women's literature in America, 1820-1860 - Grasso, Linda M. (Gender & American culture., 2002)
In this study, Linda M. Grasso demonstrates that using anger as a mode of analysis and the basis of an aesthetic transforms our understanding of American women's literary history. She explores how black and white 19th-century women writers defined, expressed and dramatized anger.